2003
DOI: 10.1152/japplphysiol.00051.2003
|View full text |Cite
|
Sign up to set email alerts
|

Finger dexterity, skin temperature, and blood flow during auxiliary heating in the cold

Abstract: The primary purpose of the present study was to compare the effectiveness of two forms of hand heating and to discuss specific trends that relate finger dexterity performance to variables such as finger skin temperature (T(fing)), finger blood flow (Q(fing)), forearm skin temperature (T(fsk)), forearm muscle temperature (Tfmus), mean weighted body skin temperature (Tsk), and change in body heat content (DeltaH(b)). These variables along with rate of body heat storage, toe skin temperature, and change in rectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 24 publications
1
29
2
Order By: Relevance
“…Dexterity is decreased when finger temperatures are less than 16 0 C (Clark, 1961;Havenith et al, 1995;Gaydos and Dusek, 1958) and sometimes even when the hands are air-cooled to 19.1 0 C (Lockhart et al, 1975). Even though Millls (1957), Lockhart and Kiess (1971), and Teichner (1957) have not always found an association between finger dexterity and finger temperature during cold exposure, Brajkovic and Ducharme (2003) found that finger temperature is a more important indicator of finger dexterity compared with finger blood flow.…”
Section: Introductionmentioning
confidence: 98%
“…Dexterity is decreased when finger temperatures are less than 16 0 C (Clark, 1961;Havenith et al, 1995;Gaydos and Dusek, 1958) and sometimes even when the hands are air-cooled to 19.1 0 C (Lockhart et al, 1975). Even though Millls (1957), Lockhart and Kiess (1971), and Teichner (1957) have not always found an association between finger dexterity and finger temperature during cold exposure, Brajkovic and Ducharme (2003) found that finger temperature is a more important indicator of finger dexterity compared with finger blood flow.…”
Section: Introductionmentioning
confidence: 98%
“…These parameters have been T ha and T fi , body heat content (H b ) and changes in body heat content (∆H b ) [7][8][9][10] . Gaydos and Dusek 10) looked at the effect of local versus total body cooling and concluded that T fi seemed to be the primary determinant of impaired manual performance.…”
Section: Introductionmentioning
confidence: 99%
“…They further showed that ∆H b is a better indicator of relative changes in extremity temperature and finger dexterity than rate of body heat storage. Brajkovic et al 7) tested the effect of direct hand heating (heated gloves) and indirect heating (heated vest). They found that during three hours of exposure to -25°C it is possible to maintain finger dexterity by means of both indirect and direct hand heating in spite of a negative rate of body heat storage during direct hand heating.…”
Section: Introductionmentioning
confidence: 99%
“…Manual dexterity is frequently used to evaluate hand function and is important during hand manipulation. Hand/finger skin temperature is considered a vital factor in dexterity (Schiefer et al, 1984;Enander, 1984;Enander & Hygge, 1990;Brajkovic & Ducharme, 2003, Chen et al, 2010 and hand performance (Riley & Cochran, 1984;Havenith et al, 1995, Chen et al, 2010. More importantly, such impairment may lead to an increased number of accidents (Müller, 1982; cited by Havenith et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Wearing gloves could delay the reduction in FST and reduce the perception of pain (Suizu et al, 2004;Suizu & Harada, 2005), and it is supposed that wearing gloves could also extend ET. Consequently, it is worthwhile and interesting to identify the FST at the point of pain tolerance during cold immersion, for FST has been reported as a crucial factor affecting hand dexterity (Schiefer et al, 1984;Enander, 1984;Enander & Hygge, 1990;Brajkovic & Ducharme, 2003, Chen et al, 2010. Wolff (1984) defined pain tolerance as 'that point at which a subject will terminate or withdraw from noxious stimulation' and argued that tolerance measures in the laboratory are analogous to clinical pain.…”
Section: Introductionmentioning
confidence: 99%